Determinan Indeks Pembangunan Manusia di Pulau Jawa: Analisis Data Panel Tahun 2014-2021 - Alfiadiba Salsabila; Maulidyah Indira Hasmarini (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to examine and calculate the magnitude of the increase in the rate of development of human resource development, especially in the area of Java Island, and identify the determinants that have an influence relationship on the HDI for the 2014-2021 period. The characteristics of this research case study are quantitative. The analytical tool implemented in this research case study is the panel data approach regression analysis. Information sources for research data are accessed through the Central Bureau of Statistics, Bappenas, and the National Single Window for Investment (NSWI), defined as secondary data. The best model test was obtained from the panel data estimation results, the Fixed Effect Model (FEM). This study shows that economic growth has a negative effect on the human development index. On the other hand, population and domestic investment positively affect the human development index.